1994
DOI: 10.1063/1.111050
|View full text |Cite
|
Sign up to set email alerts
|

Short wavelength intersubband transitions in InGaAs/AlGaAs quantum wells grown on GaAs

Abstract: Investigation of short wavelength intersubband transitions in InGaAs/AlAs quantum wells on GaAs substrate

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0
2

Year Published

1997
1997
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 9 publications
1
16
0
2
Order By: Relevance
“…The third method is to use metamorphic InGaAs QWs and QDs. This approach has been widely used for electronic devices such as high electron mobility transistors and heterojunction bipolar transistors, but is seldom used for optoelectronic devices [9]. We have recently demonstrated that the metamorphic InGaAs QWs reveal strong light emission covering wavelengths in the range 1.3-1.6 μm [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The third method is to use metamorphic InGaAs QWs and QDs. This approach has been widely used for electronic devices such as high electron mobility transistors and heterojunction bipolar transistors, but is seldom used for optoelectronic devices [9]. We have recently demonstrated that the metamorphic InGaAs QWs reveal strong light emission covering wavelengths in the range 1.3-1.6 μm [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of radiation ( 0 0   ) or in a low laser field (   0 40 Å) tr E diminishes in large QWs, as expected, because the levels E 1 and E 2 move down and become closer to each other. For uncapped QW-heterostructures this result is a customary one, for example: in a GaAs/Al 0.3 Ga 0.7 As SQW with w L = 50 -65 Å (Helm, 2000), in GaAs/Al 0.3 Ga 0.7 As SQW and sPQW with w L = 100 -200 Å (Eseanu, 2010) and in a In 0.5 Ga 0.5 As/AlAs SQW with w L = 20 -100 Å (Chui, 1994). By applying an intense laser field the reduction of tr E (as function of w L ) becomes weaker, but for high laser parameter values (   0 80 Å), tr E turn to rise with w L , especially in the presence of a thick cap layer.…”
Section: Thementioning
confidence: 99%
“…Transition rates and optical absorption/gain coefficients for intersubband device operation are defined in terms of the dipole matrix elements between the two states [20]. In recent years, determination of the dipole matrix elements has been addressed in several experimental [21,22] and theoretical [23] papers. Theoretical predictions of the electronic energies and of the optical transition strengths have been mainly based on standard single-band envelope wavefunction Hamiltonians.…”
Section: Introductionmentioning
confidence: 99%